Tools for primary care patient safety: a narrative review - Spencer, Rachel; Campbell, Stephen M. (BioMed Central, 2014)
Background: Patient safety in primary care is a developing field with an embryonic but evolving evidence base. This narrative review aims to identify tools that can be used by family practitioners as part of a patient safety toolkit to improve the safety of the care and services provided by their practices.